Immediate Loading of Mandibular Overdentures Supported by One‐Piece, Direct Metal Laser Sintering Mini‐Implants: A Short‐Term Prospective Clinical Study. Issue 2 (1st February 2015) - Mangano, Francesco G.; Caprioglio, Alberto; Levrini, Luca; Farronato, Davide; Zecca, Piero A.; Mangano, Carlo
Abstract : Background: Only a few studies have dealt with immediately loaded, unsplinted mini‐implants supporting ball attachment–retained mandibular overdentures (ODs). The aim of this study is to evaluate treatment outcomes of ball attachment–retained mandibular ODs supported by one‐piece, unsplinted, immediately loaded, direct metal laser sintering (DMLS) mini‐implants. Methods: Over a 4‐year period (2009 to 2012), all patients referred to the Dental Clinic, University of Varese, and to a private practice for treatment with mandibular ODs were considered for inclusion in this study. Each patient received three or four DMLS mini‐implants. Immediately after implant placement, a mandibular OD was connected to the implants. At each annual follow‐up session, clinical and radiographic parameters were assessed, including the following outcome measures: 1) implant failures; 2) peri‐implant marginal bone loss; and 3) complications. Statistical analysis was conducted using a life‐table analysis. Results: A total of 231 one‐piece DMLS mini‐implants were inserted in 62 patients. After 4 years of loading, six implants failed, giving an overall cumulative survival rate of 96.9%. The mean distance between the implant shoulder and the first visible bone‐to‐implant contact was 0.38 ± 0.25 and 0.62 ± 0.20 mm at the 1‐ and 4‐year follow‐up examinations, respectively. An incidence of 6.0% of biologic complications was reported; prosthetic complications were more frequent (12.9%). Conclusions: Within the limits of this study, it can be concluded that the immediate loading of one‐piece, unsplinted, DMLS titanium mini‐implants by means of ball attachment–supported mandibular ODs is a successful treatment procedure. Long‐term follow‐up studies are needed to confirm these results.